Formulation of Islamic Educational Thought: An Approach and Literature Review in Islamic Educational Practice - Abdul Haris Rasyidi; Ulyan Nasri; Ayatullah; Abdul Haris (Formad English Foundation NTB Jakarta, 2025)
This study examines the models of thought in Islamic education that developed in the course of Islamic intellectual history. Three main approaches are analyzed, namely: (1) the conservative school (al-Muhāfiẓ) represented by al-Ghazālī, with a focus on text-based education (naqli) and metaphysical dimensions; (2) the religious-rational school (al-Dīniy al-‘Aqlāniy) as depicted in the thoughts of the Ikhwān al-Ṣafā which emphasizes the balance between revelation and reason; and (3) the pragmatic school (al-Dzarā’i‘iy) pioneered by Ibn Khaldūn, which emphasizes the historical and sociological approach in education. The method used is a literature review with a critical examination of relevant primary and secondary sources. The results of the study show that each school has a distinctive epistemological foundation whether based on sacred texts, rationality, or empirical reality which forms a holistic conceptual framework for Islamic education. These findings contribute to the development of contemporary Islamic education curriculum by considering the integration between text, reason, and context.